Pengaruh Model Pembelajaran Logan Avenue Problem Solving (LAPS)-Heuristic Berbantuan Media Flash Card Math Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas VII SMP Negeri 1 Paguyangan - Debby Amaliah Putri; Heru Agni Setiaji (Jurnal Karya Pendidikan Matematika, 2023)
This study aims to find out the effectiveness of the Logan Avenue Problem Solving (LAPS)-Heuristic learning model assisted by flash card math media towards increasing the mathematical problem solving abilities of  grade students. This study was quantitative with a quasi-experimental type and a Nonequivalent Control Group Design. The population in this study were  grade of SMP Negeri 1 Paguyangan, total was 330 students. The sampling technique used simple random sampling. From the sampling, two classes were obtained, namely class VII G as the experimental class which was subjected to the Logan Avenue Problem Solving (LAPS)-Heuristic learning model assisted by flash card math media and class VII H as the control class which was not subjected to the model and media. In this study the instruments used were tests in the form of pretest and posttest. The results of this study there are found the differences in the average ability of students in the experimental class and the control class. This is reinforced by the average results of the experimental class more than the average results of the control class. The logan avenue problem solving (LAPS)-Heuristic learning model assisted by flash card math media was stated effective enough to improved students' mathematical problem solving abilities with the results obtained that the average percentage of N-Gain in the experimental class is 66.47% and the control class is 25.30% with an ineffective interpretation.